Factor XI and XII as antithrombotic targets - Müller, Felicitas; Gailani, David; Renné, Thomas (Current opinion in hematology, 2011)
Arterial and venous thrombosis are major causes of morbidity and mortality, and the incidence of thromboembolic diseases increases as a population ages. Thrombi are formed by activated platelets and fibrin. The latter is a product of the plasma coagulation system. Currently available anticoagulants such as heparins, vitamin K antagonists and inhibitors of thrombin or factor Xa target enzymes of the coagulation cascade that are critical for fibrin formation. However, fibrin is also necessary for terminating blood loss at sites of vascular injury. As a result, anticoagulants currently in clinical use increase the risk of bleeding, partially offsetting the benefits of reduced thrombosis. This review focuses on new targets for anticoagulation that are associated with minimal or no therapy-associated increased bleeding. Data from experimental models using mice and clinical studies of patients with hereditary deficiencies of coagulation factors XI or XII have shown that both of these clotting factors are important for thrombosis, while having minor or no apparent roles in processes that terminate blood loss (hemostasis). Hereditary deficiency of factor XII (Hageman factor) or factor XI, plasma proteases that initiate the intrinsic pathway of coagulation, impairs thrombus formation and provides protection from vascular occlusive events, while having a minimal impact on hemostasis. As the factor XII-factor XI pathway contributes to thrombus formation to a greater extent than to normal hemostasis, pharmacological inhibition of these coagulation factors may offer the exciting possibility of anticoagulation therapies with minimal or no bleeding risk.